Pengaruh Produk dan Pelayanan Terhadap Keputusan Pembelian pada Restoran Ayam Goreng Produk Lokal di Kota Malang - Deasy Chrisnia Natalia (Program Pendidikan Vokasi Universitas Brawijaya, 2018)
Restaurant business is gratly promising. Competition in this business is quite high. To win the competition, the business owner must be able to create products that meet the consumer needs. To do this, business owner has to understand consumer behaviour. This consumer behaviour is related to purchasing decision. This study is a qualitative descriptive research aiming to determine the influence of product and service to purchasing decision on local product fried chicken restaurants in Malang city. This study involved 20 customers taken from each restaurant and determined by accidental sampling method. The research result shows that the product factor with a mean value of 3.7 is the most dominant factor that affects consumers purchasing decision. Future researchers are recommended to deal with promotion factor when investigating the factors influencing consumer purchasing decision.